Acupuncture Improved the Function of the Lower Esophageal Sphincter and Esophageal Motility in Chinese Patients with Refractory Gastroesophageal Reflux Disease Symptoms: A Randomized Trial - Tang Yuming; Zhao Yuping; Lin Yihan; Zhu Ying; Huang Jia; Shen Hanbing; Zou Duowu; Yao Weiyan (Gastroenterology Research and Practice)
Objectives. Acupuncture is therapeutic for refractory gastroesophageal reflux disease by an unclear mechanism. This study was aimed at investigating the effect of acupuncture on esophageal motility in patients with symptoms of refractory gastroesophageal reflux disease. Methods. Sixty-eight patients with refractory gastroesophageal reflux disease symptoms were prospectively enrolled from August 2014 to December 2018 and randomized into acupuncture and control groups (n=33 and 35, respectively). The acupuncture group received acupuncture, and the control group received sham acupuncture. Pre- and post-acupuncture high-resolution manometry was performed to evaluate the effect of acupuncture on esophageal motility. The GerdQ questionnaire was used to evaluate the pre- and post-intervention symptoms. Results. After acupuncture, there was a significant increase in the length of lower esophageal sphincter (3.10±1.08 cm vs. 3.78±1.01 cm), length of intra-abdominal lower esophageal sphincter (2.14±1.05 cm vs. 2.75±1.16 cm), and mean basal pressure of lower esophageal sphincter (22.02±10.03 mmHg vs. 25.06±11.48 mmHg) in the acupuncture group (P=0.014); moreover, the numbers of fragmented contraction and ineffective contraction decreased from 36 to 12 (P<0.001) and 43 to 18 (P=0.001), respectively, in the acupuncture group. However, no significant difference was observed in the control group. The GerdQ score decreased significantly from 9.45±2.44 to 7.82±2.21 points in the first week after acupuncture (P<0.001). Conclusions. Acupuncture, which improves esophageal motility, has short-term efficacy in patients with symptoms of refractory gastroesophageal reflux disease. This trial is registered with Chinese Clinical Trial Registry (ChiCTR1800019646).